2018
DOI: 10.3390/su10082665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Long-Term SOC and Crop Productivity within Conservation Systems Using GFDL CM2.1 and EPIC

Abstract: Abstract:Will soil organic carbon (SOC) and yields increase for conservation management systems in tropical zones in response to the next 100 years? To answer the question, the Environmental Policy Integrated Climate (EPIC) model was used to study the effects of climate change, cropping systems, conservation agriculture (CA) and conservation tillage management practices on SOC and crop productivity in Kampong Cham, Cambodia. The EPIC model was successfully calibrated and validated for crop yields, biomass, SOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Previous studies revealed that rice demand is rising by~1.8% per year [3,5]. It is challenging to increase rice production with limited land and water resources [5,6], especially under the conditions of extreme floods and weather driven by climate change [7][8][9][10]. The Mekong Delta is vulnerable to water regime changes and seawater intrusion [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that rice demand is rising by~1.8% per year [3,5]. It is challenging to increase rice production with limited land and water resources [5,6], especially under the conditions of extreme floods and weather driven by climate change [7][8][9][10]. The Mekong Delta is vulnerable to water regime changes and seawater intrusion [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater is one of the most important finite natural resources for fresh water on Earth [1][2][3]. Its importance has increased as people depend on it for agriculture and industry, with domestic use exponentially increasing [4][5][6][7][8]. Groundwater exploration and climate change in recent years have led to accelerated depletion of groundwater levels as well as deterioration of groundwater quality, especially in shallow aquifers [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, crop rotation has been identified as a good practice that can aid in carbon sequestration in this era of climate change. Le et al [16] observed that carbon sequestration has more sensitivity to the cropping system than climate change, and this implies that with the effective practice of crop rotation, climate change may not significantly affect crop production. Farina et al [17] in another study on the adaptation of agricultural systems to climate change, with particular reference to the effect of Durum wheat-based rotation on soil organic carbon (SOC) and nitrogen, showed that losses were greatly reduced even though crop rotation has no significant negative effect on the SOC.…”
Section: Introductionmentioning
confidence: 99%